Molecular translocation between parasitic plants and their hosts - Chen, Yuchao; Wu, Huilan; Cai, Jie; Guo, Shenghu; Gan, Xiaoyan; Liu, Xuan; Yang, Jianguo (Frontiers in Plant Science, 2025)
Parasitic plants are a special group deriving their nutrients from another plant, some of which such as witchweeds (Striga spp.) and broomrapes (Orobanche and Phelipanche spp.) are referred as weeds responsible for severe crop losses in agriculture. The parasite attaches to and feeds off its host using a haustorium, which also facilitates the transport of various molecules between the parasite and its host. These translocation molecules have received extensive attention from researchers. In this review, we summarize the existing knowledge on the transfer of molecules such as pathogens, herbicides, RNAs, and proteins between parasitic plants and their hosts, and discuss their potential implications. Additionally, we provide an overview of horizontal gene transfer (HGT) between species, which is particularly evident in the mitochondrial and nuclear genomes, with some transgenes assumed to have functional roles in their recipient species, offering new insights into the evolution of parasitic plants. Finally, we discuss the significance of parasitic plant research and the development of future research technologies to advance our understanding of plant parasitism.